A vendégek preferenciái a fenntartható szállodai attribútumokról - Ásványi, Katalin; Chaker, Hager (Közép-Európai Közlemények, 2021)
Nowadays, the hotel industry is increasingly experiencing that hotel guests are more and more looking for sustainable solutions when traveling, and to meet these expectations, hotels need to adapt by implementing sustainability initiatives. This paper aims to explore the behavior, perceptions, and consumption preferences of Hungarian hotel guests about the sustainable attributes of hotels. The main research question in this study is to determine the most important sustainability priorities of guests at hotels. We used the Q methodology to study subjective perspectives. Based on the literature, we formulated 35 statements and interpreted them along with eight categories. Three groups of opinions were formed: environmentally sustainable, limited sustainable, and self-interested sustainable. Based on the order of preference, it can be concluded that there are basically expected sustainability practices that are mostly related to the environmental pillar. At the same time, the attitudes of the respondents towards the attributes that affect the guests or are implemented with their involvement are not uniform. Among the extra expectations are elements related to the social pillar. By grouping tourists with a similar attitude towards sustainable hotels’ attributes and identifying the CSR value preferences of each group, we make suggestions for hotels on which sustainability practices they should implement, with a greater emphasis on meeting the guests’ expectations, in order to further strengthen tourists’ commitment to sustainable tourism and preference for sustainable hotels.